Reconciling Economic Theory and Economic History: The Rise of Japan - Dopfer, Kurt (Journal of economic issues, 1985)
Attention is focused on why Japan developed rapidly in the 19th century, while other Asian countries did not move along a similar development path. Analysis proceeds from a nomothetic core, the dualistic transition theory, which propounds that an agricultural surplus of factors and food constitutes the basis for an extension on nonagricultural sectors. Comparison reveals remarkably dynamic features of both the traditional systems of Japan and those of other Asian countries. Thus, the initial condition thesis does not explain why Japan made the quantum leap to a modern industrialized society. Looking for an endogenous explanation of the great transition, a successive sequence path thesis is put forth. That is, a developmental state is not possible without the preceding developmental state. In the 19th century, there existed an historical constellation that either supported or worked against a country's entrance into the evolving sequence. The historical opportunity specific to the 19th century was either to colonize or be colonized. Japan was an 11th hour entrant into the sequence, but unlike other Asian countries, it was a colonizer and not a colony.